2018
DOI: 10.1073/pnas.1813662115
|View full text |Cite
|
Sign up to set email alerts
|

Role of sexual imprinting in assortative mating and premating isolation in Darwin’s finches

Abstract: Global biodiversity is being degraded at an unprecedented rate, so it is important to preserve the potential for future speciation. Providing for the future requires understanding speciation as a contemporary ecological process. Phylogenetically young adaptive radiations are a good choice for detailed study because diversification is ongoing. A key question is how incipient species become reproductively isolated from each other. Barriers to gene exchange have been investigated experimentally in the laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 97 publications
(119 reference statements)
0
38
1
Order By: Relevance
“…A previous study of the mating patterns of the finch species on Daphne has provided evidence in support of a hypothesis of mate choice based on parental imprinting (41). According to the hypothesis, the choice of a mate is influenced by early experience of parental morphology (41)(42)(43)(44)(45). Females are expected to choose males with morphological features close to their own parents' morphology under conditions that are favorable for expressing such choice.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A previous study of the mating patterns of the finch species on Daphne has provided evidence in support of a hypothesis of mate choice based on parental imprinting (41). According to the hypothesis, the choice of a mate is influenced by early experience of parental morphology (41)(42)(43)(44)(45). Females are expected to choose males with morphological features close to their own parents' morphology under conditions that are favorable for expressing such choice.…”
Section: Resultsmentioning
confidence: 93%
“…A male-biased sex ratio implies increased opportunity for females to choose high-quality males (39). A previous study of the mating patterns of the finch species on Daphne has provided evidence in support of a hypothesis of mate choice based on parental imprinting (41). According to the hypothesis, the choice of a mate is influenced by early experience of parental morphology (41)(42)(43)(44)(45).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Experiments have shown that female but not male cichlids in the genera Pundamilia and Mbipia imprint on their mothers' phenotypes (Verzijden & ten Cate, ; Verzijden, Korthof, & Cate, ; Verzijden, Zwinkels, & Cate, )—as in case (b) above —raising the intriguing possibility that imprinting is part of the explanation of the spectacular speciosity of cichlids in the African rift valley lakes. Mate choice in Darwin's finches too is largely determined by sexual imprinting (Grant & Grant, ).…”
Section: Discussionmentioning
confidence: 99%
“…For decades, evolutionary biologists have sought to understand the links between an individual's choice of mate and reproductive isolation between populations and species 1 . Writing in Proceedings of the National Academy of Sciences, Grant and Grant 2 provide evidence suggesting that two species of Darwin's finch learn features of their parents early in life and use this knowledge to inform their choice of mate in adulthood, a process known as sexual imprinting. Their study raises fascinating questions about the roles of learning and genetics in mate choice, and how matings between similar individuals (assortative mating) drive the evolution of new species.…”
Section: E W I S G S P U R G I N and T R Ac E Y C H A P M A Nmentioning
confidence: 99%